2022
DOI: 10.1038/s41598-022-10686-y
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and a comparative transcriptomic analysis of a male-specific cell line from the African malaria mosquito Anopheles gambiae

Abstract: Cell lines allow studying various biological processes that may not be easily tractable in whole organisms. Here, we have established the first male-specific cell line from the African malaria mosquito, Anopheles gambiae. The cells, named AgMM and derived from the sex-sorted neonate larvae, were able to undergo spontaneous contractions for a number of passages following establishment, indicating their myoblast origin. Comparison of their transcriptome to the transcriptome of an A. gambiae-derived Sua5.1 hemocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Anopheline cell lines have been used to examine a wide variety of traits, including to determine if the Minos transposable element integrates in a transposase-dependent manner [ 2 ], to characterize the cellular response to Bin toxin, a candidate vector control tool [ 3 , 4 ], to study hemocyte properties and prophenoloxidase (PPO) expression [ 5 ], for studies of phagocytosis and hemocyte gene expression [ 6 ], to characterize the effect of genetic variation enhancer activity [ 7 ], to characterize interaction of proteins with a role in malaria infection [ 8 ] and to perform STARR-seq and establish a genome-wide catalog of transcriptional enhancers [ 9 ]. Establishment of a male-specific anopheline cell line suitable for the study of processes unique to male mosquitoes was also recently reported [ 10 ]. The 4a-3B Anopheles gambiae cell line is the first continuous insect cell line used to study both humoral and cellular immune responses of An.…”
Section: Introductionmentioning
confidence: 99%
“…Anopheline cell lines have been used to examine a wide variety of traits, including to determine if the Minos transposable element integrates in a transposase-dependent manner [ 2 ], to characterize the cellular response to Bin toxin, a candidate vector control tool [ 3 , 4 ], to study hemocyte properties and prophenoloxidase (PPO) expression [ 5 ], for studies of phagocytosis and hemocyte gene expression [ 6 ], to characterize the effect of genetic variation enhancer activity [ 7 ], to characterize interaction of proteins with a role in malaria infection [ 8 ] and to perform STARR-seq and establish a genome-wide catalog of transcriptional enhancers [ 9 ]. Establishment of a male-specific anopheline cell line suitable for the study of processes unique to male mosquitoes was also recently reported [ 10 ]. The 4a-3B Anopheles gambiae cell line is the first continuous insect cell line used to study both humoral and cellular immune responses of An.…”
Section: Introductionmentioning
confidence: 99%